Study of Low Density Polyethylene Melting Process and Energy Saving in Recycling Industries - Noranai, Zamri; Azman, Muhammad Muqtadir (Research Progress in Mechanical and Manufacturing Engineering, 2023)
The effects of various Polyethylene recycling methods, the temperature required during the recycling process, the time required for the Polyethylene to be completely recycled, the energy required to recycle the materials, and the reduction of waste during the recycling process. The primary objectives of this research are to study LDPE physical characteristic before beginning the process, to identify LDPE recycle melting process, to propose potential energy saving at melting process and to estimate potential energy saving. This study's scope defines the Current melting process at Kinta Recovery Recycling Sdn Bhd in order to collect data. Then, calculate the difference between the existing heater of the process and the potential energy savings if an induction heater is utilized. Consequently, conclude that conducting the injection molding process in accordance with the specified instructions will result in energy savings